2020
DOI: 10.1002/ente.202000750
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Iodine‐Functionalized Graphene Electrocatalyst Using Deep Eutectic Solvents for Oxygen Reduction Reaction and Supercapacitors

Abstract: Iodine‐functionalized reduced graphene oxide (I@RGO) as an active oxygen reduction reaction (ORR) electrocatalyst and energy‐storage material for supercapacitors is synthesized. Herein, a novel deep eutectic solvent (DES) of choline chloride and potassium triiodide is prepared. It is applied to reduce GO and for the consequential functionalization of iodine. The metal‐free iodine‐functionalized graphene is prepared by a facile method, which has a decent electrocatalytic activity for ORR. However, the triiodide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Secondary weight loss was also observed at 175-213 °C, corresponding to the decomposition of the unstable oxygen-containing functional groups for ChemistrySelect reduced graphene oxide layers and iodine groups immobilized on its surface, which in total, at the end of this stage about 17.5 % of the nanocomposite mass is lost. [22,25,29] These two steps of weight loss in GO@CoFe 2 O 4 nanocomposite were 3 % and 6 %, at temperatures of 25-110 °C and 225-315 °C, respectively. Weight loss up to 315 °C in I@rGO@CoFe 2 O 4 is about 8 % higher than in GO@CoFe 2 O 4 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Secondary weight loss was also observed at 175-213 °C, corresponding to the decomposition of the unstable oxygen-containing functional groups for ChemistrySelect reduced graphene oxide layers and iodine groups immobilized on its surface, which in total, at the end of this stage about 17.5 % of the nanocomposite mass is lost. [22,25,29] These two steps of weight loss in GO@CoFe 2 O 4 nanocomposite were 3 % and 6 %, at temperatures of 25-110 °C and 225-315 °C, respectively. Weight loss up to 315 °C in I@rGO@CoFe 2 O 4 is about 8 % higher than in GO@CoFe 2 O 4 .…”
Section: Resultsmentioning
confidence: 90%
“…A band at 592 cm À 1 was detected, which was attributed to stretching vibration of (CÀ I) and metal-oxygen bond. [22] The peaks at 1336 cm À 1 is attributed to (CÀ N) stretching. [26] Apart from these three bands, the other cases that appear in the I@rGO@CoFe 2 O 4 show a similar vibrational pattern compared to pristine GO@CoFe 2 O 4 nanosheets (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…To realize the optimized reaction condition for synthesizing the designed materials, the influence of reaction conditions on the specific capacitance at a current density of 1 A·g −1 of the thus‐synthesized materials was evaluated by using a three‐electrode system under a current density of 1 A·g −1 in KOH aqueous solution (6.0 mol·L −1 ) at room temperature. GCD curves of samples (Figure 5A) revealed that the formed PGr electrode possesses a much higher specific capacitance (268 F·g −1 ), in contrast to Gr (128 F·g −1 ), Gr‐NH 4 I (173 F·g −1 ), and Gr‐KI (201 F·g −1 ), indicating the contribution of the interconnected hierarchically porous structure induced by decomposition of KI and NH 4 I and the doping of iodine/nitrogen atoms into the graphene skeleton to double‐layer capacitance 20,33,34 . Furthermore, annealing temperature was absolutely an essential element for capacitance performance.…”
Section: Resultsmentioning
confidence: 99%
“…GCD curves of samples (Figure 5A) revealed that the formed PGr electrode possesses a much higher specific capacitance (268 FÁg À1 ), in contrast to Gr (128 FÁg À1 ), Gr-NH 4 I (173 FÁg À1 ), and Gr-KI (201 FÁg À1 ), indicating the contribution of the interconnected hierarchically porous structure induced by decomposition of KI and NH 4 I and the doping of iodine/nitrogen atoms into the graphene skeleton to double-layer capacitance. 20,33,34 Furthermore, annealing temperature was absolutely an essential element for capacitance performance. According to Figure 5B, the specific capacity values of PGr derived from calcinating temperatures of 400, 600, and 800 C were 154, 268, and 228 FÁg À1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Iodine-doped rGO could be obtained by mixing graphite oxide with PI3 followed by refluxing for 24 h. High-quality I/rGO was reported by using a ball milling time of 48 h and further freeze-drying for 48 h. Iodine-doped graphene was prepared by thermal annealing at temperatures between 500 and 1100 °C. Another method involved a high-efficient heat-pressing technique to obtain I/rGO nanosheets [ 14 ]. Our recent work reported an iodination method by electrophilic substitution starting from graphite and various oxidation agents, in the presence of different catalysts such as AlI3 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%